Effect of flow diverter stent malposition on intracranial aneurysm hemodynamics-An experimental framework using stereoscopic particle image velocimetry. - Christoph Roloff; Philipp Berg (PLoS ONE)
Background Flow-diverting stents are increasingly used for the minimally-invasive treatment of intracranial aneurysms. However, a correct positioning of such devices can be challenging due to varying vessel diameters as well as the complex anatomy of the neurovasculature. As a consequence, unsuccessful treatment outcomes are increasingly reported requiring an improvement of the understanding of stent-induced flow modification. Methods To evaluate the effect of different degrees of flow diverter stent malposition on intra-aneurysmal hemodynamic changes, a controlled hemodynamic configuration was created using an idealized intracranial aneurysms model. Afterwards, four different treatment scenarios were reproduced comprising of 1) the ideal treatment, 2) an insufficient wall apposition in the region of the ostium, 3) a distorted device migrating into the aneurysm sac and 4) an inaccurately deployed stent due to wrong release location. For the assessment of the individual flow modifications, high-resolution stereoscopic particle image velocimetry (PIV) measurements were carried out. Results The analysis of the precise in-vitro PIV measurements reveals that in all cases a considerable reduction of the cycle-averaged and peak-systolic velocity was obtained. Compared to the untreated aneurysm configuration, the flow reduction ranged from 63% (scenario 4) up to 89% (scenario 3). The ideal treatment reached a reduction of 78%, which is known to be sufficient for a successful therapy. However, inaccurate device positioning leads to increased oscillating flow towards the lateral directions reducing the chances of sufficient thrombus formation. Conclusions High-resolution in-vitro PIV measurements enable an accurate quantification of the treatment efficacy for flow-diverting devices. Furthermore, insufficient treatment outcomes can be reproduces allowing for an assessment of intra-aneurysmal hemodynamic changes.